Energy Efficiency Project for the Campuses of Unicamp - Thalita dos Santos Dalbelo; Luiz Carlos Pereira da Silva; Adriana Botelho Dieguez; Glauco Niro; Fernando Cesar Vieira; Fransisca Dulcineia da Cruz Gomes (Universitas Diponegoro, 2024)
Unicamp is making progress in making its energy consumption more efficient through partnerships with companies in the electricity sector and projects carried out within the scope of the Coordination of Sustainability. Despite already being able to report a reduction of around 10% in energy consumption during the last four years, it is important for Unicamp to be able to accelerate the transition to a more sustainable operation. The Energy Efficiency Project aims to reduce the university's electricity consumption by 30% by 2030. For this purpose, it is divided into three sub projects aimed at saving energy, modernizing, and improving buildings and the university's sustainability indicators. The Unicamp 100% Led subproject foresees the replacement of conventional lamps by 18W LED tube lamps. The Sustainability in the Air subproject aims to replace old air conditioning equipment with efficient equipment. And the + Photovoltaic subproject aims to increase the generation of photovoltaic energy on the roofs of university buildings. The main goal of this is to report the implementation process of this project, its challenges, results achieved and indicators. The result of this explanation can be used as an example so that other universities can advance in the sustainable management of electric energy.